FINANCIAL FEASIBILITY OF KERUPUK JARI PROCESSING BUSINESS IN PASIR UTAMA VILLAGE RAMBAH HILIR DISTRICT ROKAN HULU REGENCY (A Case Study Processing Business Kerupuk Jari Mr. Andika) - Aprilianto, Gatut Sudi (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
High demand for crackers making business opportunities for cracker processing business, however, in making cracker processing business entrepreneurs typically do not conduct financial records, so it is not known how the expenditure and revenue to the business. This study aims to determine the income and financial feasibility of kerupuk jari processing business. The research was conducted from December 2015 through January 2016. Data collection methods used were interviews with respondents and observations place of business. The results showed that the kerupuk jari processing business is to earn income in year 1 of Rp.36,000,000, the 2nd year of Rp.38,400,000, the 3rd year of Rp.38,880,000, 4th year of Rp.39,600,000, years -5 for Rp.40,800,000, and the 6th year of Rp.43,200,000. Results of the calculation of financial feasibility on thekerupuk jari processing businesses declared eligible by the value of the Net Present Value of Rp.42.291.568, - that is positive (NPV> 0), Internal Rate Of Return 50.29% where the IRR is greater than the applicable ie Compound Factor 12.95% Net Benefit Cost Ratio is 1.1499 where (Net B / C> 1), Pay Back Period for 6 Months 14 Days, and Break Even Point for 5 Year 1 Day. Results of sensitivity analysis of operational cost increase of 15% fixed selling prices, business as feasible, while if the selling price fell 15% fixed production costs then this business Improper run.